1975
DOI: 10.1136/bmj.4.5987.13
|View full text |Cite
|
Sign up to set email alerts
|

Transport of newborn infants for intensive care.

Abstract: electronics engineer eight miles (12 9 kin)) away. The mean birth weight of the infants was 1702 g (range 520-4040 g) and their mean gestational age was 32 weeks (range 24-42 weeks). The principal reasons for referral were low birth weight and severe respiratory illnesses. Altogether 109 (49")) of the infants needed--mechanical ventilation in transit and another 38 (17"%) needed it later. During the journey the condition of 88 (40(%) of the infants was thought to improve, in 125 (56X)") it was static and in ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1
1

Year Published

1978
1978
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 8 publications
0
12
1
1
Order By: Relevance
“…It has been stated that severity of neonatal illness and long term sequelae would worsen by the trauma of vaginal delivery and the immediate postnatal treatment (1,30). In the present study we found that hemoglobine did not increase postnatally in Group B infants with fetal pH < 7.20 in contrast to the non-acidotic groups.…”
Section: Discussioncontrasting
confidence: 53%
“…It has been stated that severity of neonatal illness and long term sequelae would worsen by the trauma of vaginal delivery and the immediate postnatal treatment (1,30). In the present study we found that hemoglobine did not increase postnatally in Group B infants with fetal pH < 7.20 in contrast to the non-acidotic groups.…”
Section: Discussioncontrasting
confidence: 53%
“…These included the obstetric factors present before delivery and extra information on ventilation and other complications after birth (table IV). We too had thought that antenatal transfer of our patients had improved their outcome; certainly the crude mortalities for the 10) 9 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) 7 (3)(4)(5)(6)(7)(8)(9) inborn, outborn, and in utero transfer groups suggested that infants transferred after birth had a higher mortality. Closer examination of 1-70) 07(02-10) 09(02-10) our study populations, however, showed that the outborn babies )-7-5) 7-2(6-7-7-4) 7-2(6-6-7-3) suypp were more immature and had a lower birth weight, and when these factors were taken into account there was no difference in the study populations.…”
mentioning
confidence: 94%
“…The large proportion of the infants in the present study and in the 1970 British Births study (Chamberlain et al 1975) who did not have their temperature recorded at all is worrying in view of the above evidence of the narrow limits of thermoneutral environment for VLBW infants. Worrying too are the reports that many of the sick, VLBW infants transported to special care baby units from elsewhere arrive with very low temperatures (Gamsu, personal communi-cation;Blake et al 1975), particularly since transport of such infants is likely to become more frequent with centralisation of care.…”
Section: Discussionmentioning
confidence: 99%